The Practice Turn-Away: Forty Years of Spoon-Feeding in Management Education - Joseph A. Raelin (Management Learning, 2009)
This article takes a whimsical look at the state of pedagogical delivery in management education over the last 40 years, and concludes that the long tradition of what the author refers to as `spoon-feeding in management education' is unlikely to end anytime soon. His case is built on neo-institutional theory, which posits that the pressures to conform to standardized classroom teaching are highly resistant based on deep-seated and long-standing consensual beliefs and traditions. The principal alternative of employing practice-based and critical approaches has been diluted in favor of the promotion of reductionist and mythological active learning strategies which, though useful, are unlikely to lead to the acquisition of prudential wisdom.
Keywords: J24; M53; M10; M12; I21; 330; Management education; Pedagogy; Institutional theory; Resistance to change; MBA education; Practice-based education; Critical theory; Action learning